Upah Jasa Plasma Breading Ikan Cupang Perspektif Hukum Ekonomi Syariah - Andi Ardiyan Mustakim; Hidayatulloh (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2023)
The Cupang fish plasma breading business seems popular in society. The price of Cupang fish plasma breading services is quite profitable because it depends on the success of the pupping process based on the number of puppies and the age of the puppies when taken back by the owner.  The purpose of this study is to analyze the transaction system and wages of Cupang fish plasma breading system from the perspective of fiqh muamalah. The type of this research is literature study. The approach used in this study was a normative juridical. Data analysis in this research was carried out in three stages, namely data reduction, data presentation, and data verification. The results of this study reveal that the terms used in the transaction are not a reference to legalize or prohibit plasma breading transactions. The transaction system carried out by Cupang fish plasma breading service providers is permissible in the perspective of fiqh muamalah because there are no elements of gambling, riba, fraud and not najis goods. The results of this study also found that the transaction pattern of Cupang fish plasma breading services uses ju'alah contract.